High‐Performance Stable Perovskite Solar Cell via Defect Passivation With Constructing Tunable Graphitic Carbon Nitride. Issue 8 (8th August 2021) - Ho, Ching-Mei; Wu, Ming-Chung; Chen, Shih-Hsuan; Chang, Yin-Hsuan; Lin, Ting-Han; Jao, Meng-Huan; Chan, Shun-Hsiang; Su, Wei-Fang; Lee, Kun-Mu
Abstract : Perovskite Solar Cells In article number 2100257, Ming‐Chung Wu, Kun‐Mu Lee, and co‐workers demonstrate an approach where two‐dimensional g‐C3 N4 is applied as a template for controlling the nucleation of the perovskite active layer. Adding the urea‐polymerized g‐C3 N4 into the perovskite active layer allows for a uniform surface morphology and a reduced trap density. Over 20% power conversion efficiency of perovskite solar cells with superior stability was achieved by the unencapsulated perovskite solar cells with g‐C3 N4 .